Assessing the Competence of Prospective Mathematics Teachers in Technology-Enhanced Differentiated Instruction for Inductive Learning - Enika Wulandari; YL Sukestiyarno; Scolastika Mariani; Masrukan (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2025)
The demands of 21st-century pedagogical competencies necessitate that Prospective Mathematics Teachers (PMTs) be proficient in the integrated application of technology and differentiation. This study aims to assess the competence of PMTs in implementing technology-enhanced differentiated instruction within an inductive learning framework, evaluated through seven key elements referencing the frameworks of Prince & Felder and Tomlinson. Utilizing a descriptive qualitative approach, this study analyzed in-depth peer teaching video recordings from the entire cohort of 15 students in a mathematics education program. The novelty of this research lies in its focus on the integrated operationalization of these three complex pedagogical elements. Data analysis was conducted rigorously using the interactive model of Miles, Huberman, and Saldana, supported by source triangulation to ensure the credibility of the findings. The results indicate that PMTs achieved high competence in inductive learning and differentiation (implemented by 93%–100% of PMTs). However, the implementation of technology-enhanced learning showed significant variance, being adequately achieved by only 67% of PMTs. It is concluded that while PMT training is robust in instructional design and differentiation strategies, the integration of technological tools requires further optimization and focused development to meet the demands of 21st-century skills.